2018
DOI: 10.1097/ccm.0000000000003208
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of Sepsis-3 Definitions and Sepsis Outcomes in Critically Ill Patients: A Cohort Study in 49 ICUs in Argentina

Abstract: Increasing severity of Sepsis-3 categories adequately tracks mortality; cardiovascular dysfunction subgroup, not included in Sepsis-3, has distinct characteristics. Sequential Organ Failure Assessment score shows adequate prognosis accuracy-contrary to systemic inflammatory response syndrome. This study supports the predictive validity of Sepsis-3 definitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
1
19
2
1
Order By: Relevance
“…Briefly, SATISEPSIS was a national, multicenter, prospective cohort study organized by the SATI and sponsored by the Argentine National Ministry of Health, beginning on July 2, 2016 and lasting for 3 months [14,15]. The study was approved by each hospital's Institutional Review Board, and informed consent was signed by patients or their relatives.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, SATISEPSIS was a national, multicenter, prospective cohort study organized by the SATI and sponsored by the Argentine National Ministry of Health, beginning on July 2, 2016 and lasting for 3 months [14,15]. The study was approved by each hospital's Institutional Review Board, and informed consent was signed by patients or their relatives.…”
Section: Designmentioning
confidence: 99%
“…SATISEPSIS was an observational study organized by the Argentine Society of Critical Care (Sociedad Argentina de Terapia Intensiva, SATI) to evaluate the performance of the new Sepsis-3 definitions [13], and to characterize the epidemiology and outcome of sepsis and septic shock in Argentina, a country belonging to the group of low and middle-income countries (LMICs) [14,15]. The aim of the present study was to assess the characteristics of the cardiovascular management, particularly regarding early resuscitation and use of intravenous fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Since the latest update of the sepsis-definition by consensus, severe infections are stratified as infections without organ dysfunction, sepsis, and septic shock [6], and this is believed to allow a reliable risk stratification of these patients regarding their in-hospital mortality [7]. However, sequelae and long-term outcome may not only relate to acute organ dysfunction, but rather to a "dysregulated", long lasting host immune response that may explain the high mortality with severe infections [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…In very good agreement with sepsis-3 validation study, we observed moderate discrimination capacity of SOFA applications for in-hospital mortality in infected patients (AUROC for SOFA and SOFA_change respectively: 0.75 and 0.70 in our data while 0.74 and 0.70 in sepsis-3 [9]) that was higher than SIRS' AUROC for in-hospital mortality. Further studies in the ICU setting replicating this evaluation approach also reported comparable results [29,31,32,37]. However, the use of AUROC for the assessment of risk prediction in general [57] and for sepsis-3 validation in particular [17,58] was criticized.…”
Section: Associations Of Sepsis Criteria With In-hospital Mortalitymentioning
confidence: 88%